Story Telling As An Approach to Improve Students Speaking Achievement - Abdul Aziz Rifa'at (English Education Study Program Faculty of Teacher Training and Education, 2018)
Speaking is the big problem of students in non-English major to be taught. Once the students are asked to practice speaking, they seem to be anxious and do not know what should be spoken. Storytelling is one of the alternative techniques to solve this problem. The aim of this study was to find out the significant difference between students’ speaking achievement after they were taught by using storytelling technique. The quasi-experimental study was the method of the study. The one group pretest-posttest design approach was used in this study. The study was conducted to fourth semester S1 Nursing students at STIK Siti Khadijah Palembang. The population of the study was all fourth semester S1 Nursing students at STIK Siti Khadijah Palembang in 2017. The total number of the population was 96 students. The sample of the study was 24 fourth semester S1 Nursing students at STIK Siti Khadijah Palembang in 2017. Systematic sampling was used to collect the sample. The test was administered twice as pre-test and post-test. The results of the tests were analyzed by using t-test through SPSS (Statistical Package for Social Sciences) program. The result of the study showed that there was a significant difference in speaking achievement before and after applying a conversation class based on a paired sample t-test